The Role and Importance of The Kvalimetric Formation in The Future Elementary Teachers’ Life - Sh Hudoyqulova (Universitas Muhammadiyah Sidoarjo, 2018)
This paper makes investigation on the role and importance of the kvalimetric formation in the future elementary teachers’ life. On this way, teaching methods of the Uzbek elementary education were analyzed. Major points of the development were seen in the future perspective.